Low-loss electromagnetic composites for RF and microwave applications - Wang, Hong (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2011)
Low-loss electromagnetic composites with high permittivity and permeability will benefit the miniaturization and multifunctional of RF devices. A kind of low-loss dielectric-magnetic ceramic-ceramic composite was developed by hybrid processing technology with the goal of integrating the dielectric properties and magnetic properties. The hybrid processing technology exhibits the advantage of lowered sintering temperatures for the composites while retaining good microstructure and high performance. By introducing elastomer as matrix, a kind of flexible low-loss dielectric-magnetic ceramic-polymer composite was prepared and studied. The obtained flexible dielectric-magnetic ceramic-polymer composite exhibited low loss and good mechanical properties. The results show good effects on lowering the dielectric loss and extending the cut-off magnetic frequency of the electromagnetic composite. Methods for tailoring the properties of the multifunctional composites were proposed and discussed